Sequence heterogeneity and phylogenetic relationships between the copia retrotransposon in Drosophila species of the repleta and melanogaster groups - De Almeida, Luciane M.; Carareto, Claudia M. A. (Edp Sciences S A, 2006)
Although the retrotransposon copia has been studied in the melanogaster group of Drosophila species, very little is known about copia dynamism and evolution in other groups. We analyzed the occurrence and heterogeneity of the copia 5' LTR-ULR partial sequence and their phylogenetic relationships in 24 species of the repleta group of Drosophila. PCR showed that copia occurs in 18 out of the 24 species evaluated. Sequencing was possible in only eight species. The sequences showed a low nucleotide diversity, which suggests selective constraints maintaining this regulatory region over evolutionary time. on the contrary, the low nucleotide divergence and the phylogenetic relationships between the D. willistoni/Zaprionus tuberculatus/melanogaster species subgroup suggest horizontal transfer. Sixteen transcription factor binding sites were identified in the LTR-ULR repleta and melanogaster consensus sequences. However, these motifs are not homologous, neither according to their position in the LTR-ULR sequences, nor according to their sequences. Taken together, the low motif homologies, the phylogenetic relationship and the great nucleotide divergence between the melanogaster and repleta copia sequences reinforce the hypothesis that there are two copia families.
Keywords: copia retrotransposon; nucleotide diversity; copia families